Procurement principles and management in the digital age - Baily, Peter J. H.; Farmer, David H.; Crocker, Barry; Jessop, David (2022)
"The twelfth edition has been substantially updated with many additions in the form of more detailed case studies, additional academic content and the inclusion of more practical examples of best practice in many key areas. Some of them are: the inclusion of three self-assessment tasks at the end of each chapter; a comprehensive review of the future of procurement; material explaining the long-term changes in strategy in response to supply disruptions caused by disasters and by the Covid pandemic inserted into various chapters; a revised chapter considering Industry 4.0 tools such as e-procurement, Blockchain, the Internet of Things, Big Data, artificial intelligence (AI), bots, digitalisation and analytics; diversity and supplier diversity considered in detail; the inclusion of supply chain resilience approaches; considerable coverage of sustainability provided across relevant chapters; the inclusion of social value strategies and approaches; the inclusion of virtual negotiation approaches in response to the growing trend of working from home; in the wake of the Covid pandemic, updated additional material exploring offshoring/onshoring; third sector/not-for-profit procurement considered; additional material for coverage of risk; consideration of just-in-case inventory as a method of improving resilience; the inclusion of the procurement of consultancy; the inclusion of a Contract Management Cycle; retail procurement completely revised to include omnichannel challenges and digital tools; supplier relationship management (SRM) expanded to include two-way, 360-degree relationship measurement; the addition of quality function deployment (QFD) and the House of Quality (HOQ); ratio analysis for analysing financial viability of suppliers now included"--
Includes index.
Keywords: Purchasing -- Management; Industrial procurement -- Management